A COMPREHENSIVE REVIEW OF CURRICULUM EFFICACY AND CLINICAL READINESS IN ASSESSING THE IMPACT OF HEALTH ASSISTANT TRAINING PROGRAMS ON ANAESTHESIA, RADIOLOGY, AND DIAGNOSTIC X-RAY INTEGRATION. - 1.Abdalhameed Mohammad Alhamidi | 2.Rhma Salem AsemrAlazmi | 3.Duaa Muhammed GhanemAlsharari | 4.MajedSayahAlazmi | 5.MenwarSubairAlrowily | 6.Alwaleed Abdullah Alwushayh | 7.HamadSulimanAlazmi ,; 8. Mohammed obaidalazmi | 9.‏Suliman mohammed alsharari | 10. Ahmed Hamed S Alsharari | 11.Yasr Abdullah S Al-Sharari | 12.Mohammed Daefallh M Al sharari, (Chelonian Research Foundation, 2022)
Nursing aide training upsurges are paramount to remedying healthcare human resource scarcity, particularly in vulnerable countries. The scrutiny will focus on integrating these disciplines into the curriculum, emphasizing preparedness for clinical practice in areas like anesthesia, radiology, and diagnostic X-rays. A systematic review of existing literature sources—peer-reviewed articles, grey literature, and policy documents—will help define current training trends, challenges, opportunities for health assistants, and critical topics for training program development. The review emphasizes the need for standardized core curricula, competency-based assessment, and quality mechanisms to ensure the success and durability of these programs. Undoubtedly, up skilling health assistants through relevant training programs has a great potential to do this. However, there are still issues related to how the contents of the training curriculum will be designed, what they will do in the clinics, and how they will be evaluated as good professionals. For example, problems as broad as elitism, commercialization, and environmental pollution may also affect the effectiveness and sustainability of these projects. Policymakers, educators, and healthcare providers are advised to be critical players in improving current training programs and boosting the long-term impact on patients, health systems, and workforce development. We will conduct further research to determine whether this change affects patient outcomes in the long term. KEYWORDS: Health assistant, training programs, Anaesthesia, radiology, diagnostic X-ray, curriculum efficacy, clinical readiness Introduction